Synthesis And Mesomorphic Properties Of Symmetric And Non-Symmetric Multi-Functionalized Oligomers - Hng, Tiang Chuan (2009)
Six series of novel symmetric and non-symmetric oligomers with multi-functional groups have been synthesized and characterized. The oligomers comprise two series of non-symmetric dimers, three series of symmetric trimers and one series of non-symmetric trimers. Enam siri oligomer bersimetri dan tidak bersimetri dengan pelbagai kumpulan berfungsi telah disintesis dan dicirikan. Oligomer ini terdiri daripada dua siri dimer tidak bersimetri, tiga siri trimer bersimetri dan satu siri trimer tidak bersimetri